Cooperation of the Kabardino-Balkarian branch of the Soviet committee for cultural relations with compatriots abroad with non-governmental organizations of foreign Circassian diasporas in the so-cialistic times (1966-1991) - A. V. Kushkhabiev (Кавказология, 2025)
It was revealed that in 1966-1991 years the Kabardino-Balkarian branch of the Soviet Committee for Cultural Relations with Compatriots Abroad (KBB), with the support of the authorities of Kabardino-Balkarian Republic, conducted activities to promote socialist ideology in foreign Circassian diasporas to increase among them supporters of the USSR and adherents of the socialist system. During the period of perestroika (1985-1991), the work of the KBB comprised explaining to foreign compatriots the essence of reforms in the USSR and attracting investors from among them. The activities and methods used by the KBB turned out to be quite effective: in the foreign Circassian diasporas the share of supporters of the USSR, persons maintaining ties with organizations and citizens of the autonomies of the North Caucasus, members of the communist parties of Syria and Jordan, youth democratic organizations, the Arab Socialist Renaissance Party increased. The activities of the KBB contributed to the strengthening of friendly relations between the USSR and the countries of residence of compatriots, mainly with Jordan and Syria. Contacts (exchanges of delegations and tourist groups, education of youth of foreign compatriots in the universities of the KBASSR, organization of recreation for children of foreign compatriots in pioneer camps and sanatoriums of the republic, systematic correspondence of the KBB and residents of the republic with foreign compatriots) of representatives of foreign Circassian diasporas with their historical homeland, supplies to foreign compatriots of printed, video and audio materials, broadcasting radio programs to the Circassian diasporas in the countries of the Middle East were mainly performed in the Circassian language, which largely contributed to the preservation of the ethno-cultural specifics of the foreign Circassian diasporas. The cooperation of the KBB with non-governmental organizations (NGO) of foreign compatriots also contributed to the study of the Russian language, Russian and Soviet culture by a considerable number of them.